2016
DOI: 10.1016/j.jval.2016.09.821
|View full text |Cite
|
Sign up to set email alerts
|

Cadth’s $50,000 Cost-Effectiveness Threshold: Fact or Fiction?

Abstract: and Switzerland) and on peer-reviewed publications through PubMed. For Italy and Spain, a prominent regional HTA was evaluated, Lombardy and Catalonia respectively. Over 350 HTA characteristics, attributes assessed and methodologies used were assessed. Results: Among 10 HTA systems evaluated, England & Wales (NICE), Netherlands (CVZ) and Poland (AOTM) use explicitly stated incremental cost-effectiveness ratio (ICER) thresholds of £20,000-£30,000/QALY, € 40,000/QALY and € 26,500/QALY respectively. Three markets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…Of the 58 indications, 31 (53%) fell under this category for CADTH, whereas only 3 (5%) indications were solely recommended. As CADTH has not publicly stated its threshold, 18,19 what they deem an acceptable level of cost-effectiveness is unknown. The Canadian Agency for Drugs and Technologies in Health "recommend if costeffectiveness is improved" guidance could potentially be a "not recommended" guidance from NICE, as their approval processes slightly differ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 58 indications, 31 (53%) fell under this category for CADTH, whereas only 3 (5%) indications were solely recommended. As CADTH has not publicly stated its threshold, 18,19 what they deem an acceptable level of cost-effectiveness is unknown. The Canadian Agency for Drugs and Technologies in Health "recommend if costeffectiveness is improved" guidance could potentially be a "not recommended" guidance from NICE, as their approval processes slightly differ.…”
Section: Discussionmentioning
confidence: 99%
“…Cost-effectiveness was discussed under the "Committee Discussions" section of appraisals for NICE, with a threshold of £30 000 per quality-adjusted life year, 17 and the "Economic Evaluation" section for CADTH, with no explicit threshold. 18,19 Budget impact analyses were not included in the analysis, as it is not an explicit criterion for NICE, and CADTH considers it alongside cost-effectiveness analyses. A drug was classified as orphan if it targeted a disease with a prevalence of 5 or fewer per 10 000 in the European Union.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, a value of 50,000 CAD/QALY based on precedent is often cited. Griffiths et al [86] suggested, from retrospective analysis, that the value is considered when decisions state a need for reductions in prices (to achieve the ICER < 50,000 CAD/QALY) or to reinforce the decision (the ICER was under 50,000 CAD/QALY). Other interventions with higher ICERs were also recommended during the study period, demonstrating that the cost-effectiveness is not a sine qua non condition for recommendation.…”
Section: Canadamentioning
confidence: 99%
“…Additional sensitivity analyses were performed, in which treatment effects (dose, hazard and rate ratios) were applied, regardless of whether they were statistically significant or not, and the glargine U100 distribution of individual MACE components was applied to both arms. Alternative disutilities were explored for cardiovascular events and severe hypoglycaemia, and analyses were conducted in which a utility associated with the flexible dosing of degludec was captured …”
Section: Methodsmentioning
confidence: 99%
“…Alternative disutilities were explored for cardiovascular events and severe hypoglycaemia, and analyses were conducted in which a utility associated with the flexible dosing of degludec was captured. [32][33][34][35] In an additional sensitivity analysis, long-term costs and clinical outcomes with degludec vs glargine U100 were simulated over a Table S4. 36 Cost and effectiveness outcomes, the latter expressed in QALYs, were attached to each of the four scenarios detailed in Figure S2 and did not vary between treatment arms.…”
Section: Sensitivity Analysesmentioning
confidence: 99%